Contact wear of artificial denture teeth. Issue 2 (April 2018) - Preis, Verena; Hahnel, Sebastian; Behr, Michael; Rosentritt, Martin
Abstract: Purpose: High wear resistance of denture teeth preserves good occlusal relationship and sufficient parafunctional stability. This in-vitro investigation aimed to determine and compare the wear performance of different artificial denture teeth. Methods: Denture teeth of fifteen commercial products ( n  = 8/group) were loaded in a pin-on-block design using steatite antagonists (d = 3 mm). Cyclic loading (50 N) was applied for 120, 000 loadings ( f  = 1.2 Hz) with simultaneous thermal cycling (distilled water, 5 °C/55 °C, 2 min/cycle). A loading cycle consisted of a vertical 1 mm impact and a subsequent lateral 1 mm sliding movement. Worn areas were digitalized (3-D-laser-scanning-microscope). Maximum and mean wear depth and surface roughness were determined and statistically compared (one-way Anova, Tukey-HSD test, α  = 0.05). Worn surfaces and cut specimens were investigated with scanning electron microscopy (SEM). Results: Maximum wear varied between 475.1 μm and 1232.2 μm. Mean wear was between 241.1 μm and 753.6 μm with significant differences ( p  < 0.001) between individual materials. Mean and maximum wear showed a significant correlation (Pearson's correlation coefficient: 0.942). Surface roughness increased between unworn to worn surface by 1.2 μm (Ra, p  = 0.387) and by 41.7 μm (Rz, p  = 0.000). All materials provided round or drop-shaped wear traces. Superficial analysis showed no cracks, chipping or fractures in the worn areas. Detailed evaluation of cut specimens with SEM exposed cracks on the bottom of the wear traces. Conclusions: Denture teeth showed significantly different in-vitro wear performance and increased roughness in the wear trace. Differences may be attributed to the composition of the materials, regarding both filler and polymer structure. The selection of teeth might contribute to enhanced in-vivo performance of the denture.